The Concept of Tawassuṭ and Religious Moderation in the Perspective of the Qur’an and Hadith: Principles of Balance, Justice, and the Rejection of Extremism - Hary Nurdi; Mahyuddin Barni; Abdul Basir; Ali Muammar (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to examine the concept of tawassuth and religious moderation based on Islamic doctrinal sources and to analyze their relevance to the dynamics of Muslim life in the contemporary era. Using the library research method, this study finds that religious moderation represents an integral theological and ethical framework in Islam, as well as a solution to various modern religious issues such as intolerance, social polarization, and misunderstandings of religious doctrine. The findings affirm that tawassuth is not merely a moral value, but a foundational religious principle that is inclusive, adaptive, and supportive of the creation of a harmonious and civilized social order. Tawassuth, or the attitude of moderation, constitutes a principal teaching in Islam that emphasizes balance, justice, and the avoidance of extremism in religious practice. From the perspective of the Qur’an and Hadith, religious moderation is understood as the ideal identity of the Muslim community, as reflected in the concept of ummatan wasathan in Qur’an Surah al-Baqarah [2]:143. This concept teaches the importance of practicing religion proportionally neither excessively (ifrâṭ) nor negligently (tafrîṭ) while upholding values of public good, tolerance, and social responsibility. The Hadith of Prophet Muhammad (peace be upon him) further emphasizes the importance of simplicity, prudence in religious practice, and the prohibition of radicalism and fanaticism that may undermine social harmony